PENGARUH CITRA MEREK DAN KUALITAS PRODUK TERHADAP KEPUASAN PELANGGAN MELALUI KEPUTUSAN PEMBELIAN TEH PUCUK HARUM DI KOTA BEKASI - Ramadhania, Rismawati; Ali, Hapzi; Khan, Muhammad Asif; Sawitri, Ni Nyoman; Navanti, Dovina (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
The influence of brand image and product quality on customer satisfaction through purchasing decisions for Pucuk Harum Tea in Bekasi City. This research uses a quantitative approach through the Accidental Sampling technique for sampling. A total of 135 people in the city of Bekasi focusing on North Bekasi who had used Teh Pucuk Harum products were the research samples. Data examination uses the Partial Least Square (PLS) SEM method on SmartPLS 4.0. The research findings reveal the following: 1.) Brand Image has a significant effect on Purchasing Decisions, 2.) Brand Image has a significant effect on Customer Satisfaction, 3.) Product Quality has a significant effect on Purchasing Decisions, 4.) Product Quality has no significant effect on Customer Satisfaction, 5.) Purchasing Decisions have a significant effect on Customer Satisfaction.